Islamic Republic of Afghanistan : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
Although Afghanistan has made significant gains over the years, vulnerabilities remain. The economic program Afghanistan National Development Strategy (ANDS) has been developed to sustain democracy, reduce poverty, and improve growth. ANDS, an important milestone in the rebuilding and development of Afghanistan, serves as its Poverty Reduction Strategy Paper (PRSP) and uses the pillars, principles, and benchmarks of the Afghanistan Compact as a foundation to achieve its MDGs. It has given high priority to the security sector for implementing security policies and strategies and also for building an Afghan National Army for the country's security.